Dekonstruksi Normatif Asas Ne Bis In Idem dalam Tindak Pidana Korupsi Berjaringan: Studi Terhadap Dualisme Sanksi Administratif dan Pidana - Adi Abdi Rohman Haji Ali; Dwi Wachidiyah Ningsih; Dinda Heidiyuan Agustalita (Cattleya Darmaya Fortuna, 2026)
This research is driven by the difficulty of enforcing laws against corruption crimes that involve large, complicated networks. Often, there is a mix between the penalties given by government agencies like the Corruption Eradication Commission (KPK) or other supervisory bodies, and the legal actions taken in court. This situation could break the rule of ne bis in idem, which is a key legal idea that stops someone from being punished twice for the same issue. The goal of this study is to examine how the principle of ne bis in idem is applied in cases involving networked corruption. It does this by looking at how different rules work together and where the line is between penalties given by administrative bodies and those imposed by the criminal justice system. The study uses normative legal research, looking at laws, ideas, and specific court cases to understand related decisions. The study shows that some rules in different sectors are unclear about what is allowed, which can let authorities give punishments like money payments or bad conduct records that are similar to criminal penalties, either before or during a criminal case. This study finds that a more forward-thinking approach to interpretation and better alignment of rules are necessary to effectively stop violations of the principle of ne bis in idem, ensuring legal certainty and protecting the constitutional rights of people involved in corruption cases.